Hashtag Trend Analysis On Tiktok: Building Engagement In Beauty Product Sales - Indriani, Nanin; Wulandari, Sri; Andriany, Dian (International Journal of Social Service and Research, 2025)
In the digital era, including in the beauty industry, one of which is the MS Glow beauty product. TikTok, as a short video-based platform, allows brands to reach a wide audience through hashtag strategies. This study aims to analyze hashtag trends in increasing engagement towards the sale of beauty products and their impact, with a case study on the MS Glow brand. This study uses a descriptive qualitative approach with observation, documentation, and literature study methods. Lev Manovich's New Media theory is used to analyze the elements of numerical representation, modularity, automation, variability, and transcoding. The results of the study show that the use of hashtags on MS Glow products such as #msglow, #msglowskincare, and #msglowreview is able to build consumer engagement in the form of likes, comments, and reviews and can have an impact on improving product purchase decisions.